Evaluation of The Significance Grades of The Problems Experienced by Mathematics Teachers in Distance Education in The Covid-19 Pandemic by The Entropy Method - Bahadır, Oğuzhan; Türkmençalıkoğlu, Hande; Bonyah, Ebenezer (Indonesian Journal of Science and Mathematics Education, 2022)
The entropy formula, created by Claude E. Shannon using probability calculations, is an essential and objective measurement method used in multi-criteria decision-making. The purpose this study was to evaluate the problems experienced by mathematics teachers during the Covid-19 and the degree of importance of these problems were determined. Expert opinions were used to identify the problems. In the study, the ‘Entropy’ method was used to determine the degree of importance of the problems. After determining the problems, a questionnaire was applied to 22 teachers working in different geographical regions of Turkey and with different service lengths. According to the entropy results, it has been determined that the most critical problem faced by mathematics teachers in the distance education process is the ‘communication problem’ between students and teachers. In conclusion, mathematics teachers must find the right learning method to overcome communication problems so that in the future, distance learning will not experience obstacles.